1988
DOI: 10.1139/y88-227
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of inhibitory innervation in porcine colonic circular muscle

Abstract: Effects of stimulation of intramural nerves in the circular smooth muscle layer of the porcine colon (Sus scrofa domestica) were studied using the sucrose-gap technique. Electrical field stimulation of the preparation, superfused with Krebs solution at 21 degrees C, induced a transient hyperpolarization of the smooth muscle cell membrane. This hyperpolarization was an inhibitory junction potential (IJP). The responses obtained from circular muscle originating from either the centripetal or centrifugal gyri of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

1991
1991
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 0 publications
0
21
0
Order By: Relevance
“…The identity of the NANC inhibitory neurotransmitter mediating the IJP in the porcine intestine is not completely known, despite the importance of the pig as a potential source for intestinal xenotransplantation to humans. In the ileum and colon of this animal, the NANC IJP was previously shown to consist of only a fast hyperpolarization and that an increase in small conductance Ca 2+ ‐activated K + outward current is involved in the IJP 28,31 . Adenosine‐5‐triphosphate is considered the NANC inhibitory neurotransmitter in ileum but not in the colon of the pig 28,31 .…”
Section: Introductionmentioning
confidence: 77%
See 3 more Smart Citations
“…The identity of the NANC inhibitory neurotransmitter mediating the IJP in the porcine intestine is not completely known, despite the importance of the pig as a potential source for intestinal xenotransplantation to humans. In the ileum and colon of this animal, the NANC IJP was previously shown to consist of only a fast hyperpolarization and that an increase in small conductance Ca 2+ ‐activated K + outward current is involved in the IJP 28,31 . Adenosine‐5‐triphosphate is considered the NANC inhibitory neurotransmitter in ileum but not in the colon of the pig 28,31 .…”
Section: Introductionmentioning
confidence: 77%
“…The present findings showed that IJPs in porcine jejunum had only a fast component and this fast component was dependent on the opening of small conductance Ca 2+ ‐dependent K + channels sensitive to apamin. Previous studies of porcine ileum and porcine colon 28,31 showed that IJPs in these regions also consist of only a fast component. Thus, it appears that the IJP in the circular muscle layer of the pig intestine is different from the IJP in the intestine of other mammals, including humans, where it consists of both fast and slow hyperpolarizing components.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…The ascending contraction of the reflex is believed to be mediated by tachykinin motor neurons as well as cholinergic motor neurons [14]. There is strong evidence that the inhibitory response seen below the stim ulus is mediated by a VIPergic motor neuron [14,15], even though this concept has been challenged lately [27], Therefore, the in creased release of VIP in response to intralu minal agents seen in the present study could alternatively derive from muscle motor neu rons. The pattern of VIP release during chemical stimulation seems to be different from that observed in response to distension, indicating that neurons other than those ac tivated in the distension response were also involved.…”
Section: Discussionmentioning
confidence: 71%